Relating the midbrain dopaminergic system to hippocampal cell assembly dynamics associated with spatial memory function - McNamara, C (2015)
Central to the understanding of memory is a detailed understanding of the processes contributing to how some information is retained as memories, yet other information is not. Relevant to this is the question, does value and saliency information coded by dopaminergic neurons of the ventral tegmental area (VTA) affect hippocampal memory function and how might this arise? In order to address this question, I performed large scale extracellular recordings combined with optogenetic activation of dopaminergic neurons in mice. Tetrodes were located in the VTA and pyramidal cell layer of the CA1 subfield of the dorsal hippocampus. Midbrain dopaminergic neurons were made to express a chimeric protein formed of the light activated ion channel channelrhodopsin-2 and enhanced yellow florescent protein (ChR2-eYFP) through injection of a Cre activated viral construct in the VTA of DAT-IRES-Cre+/- mice. Mice explored familiar and novel open fields in the presence or absence of photostimulation. Periods of sleep and rest were recorded before and after each exploration in order to calculate the reactivation strength of hippocampal waking firing activity during subsequent sleep; a process thought to aid the stabilisation of representations enhancing their retention as memories. ChR2-eYFP expressing axons were present in the dorsal hippocampus demonstrating a direct dopaminergic projection from the midbrain to the hippocampus. Units isolated from midbrain tetrodes showed a sustained increase in mean firing rate during exploration of a novel over a familiar environment, indicating they have the potential to drive sustained dopamine release in target structures in response to such a sustained novelty cue. Hippocampal reactivation strength after exploration of a novel environment was higher than that seen after exploration of a familiar environment and this was further enhanced by burst mode photoactivation of dopaminergic neurons at their cell bodies in the VTA or at the afferent dopaminergic fibres in the dorsal CA1. A second group of mice performed a spatial learning task on a maze dubbed the 'crossword maze'. Photostimulation during learning trials did not increase the rate of learning but it did increase performance in a probe test held one hour after the end of the learning trials. Additionally, there was enhanced reinstatement of the hippocampal spatial representation during the probe test and it was preceded by enhanced reactivation of the newly formed representation in the intervening rest period. These findings reveal that midbrain dopaminergic neurons, encoding salient information about an environment, promote hippocampal network dynamics associated with memory persistence, thus modulating hippocampal memory function according to the value of the information to be remembered.